Images composition using chroma key techniques / Nurulazura Jawahir - Jawahir, Nurulazura (2014)
This project proposes a Statistical Method for solving the variation of Chroma key values respect to the background, the crucial part of this project is determining the alpha value or threshold. Therefore, Statistical Method which is Standard deviation and Mean are being used. This project approach used both foreground and background images to identify the pixel's color of the images. The alpha value need to be in range of [0, 1] to be accepted. Algorithm is implemented to retrieve the alpha value hence remove the unintended background. The algorithm is effectively can helps in reducing the green spill around the subject image. The images are evaluated based on observation made by expertise.